The Total Factor Productivity effect of related and unrelated mergers and acquisitions in the UK - Li, Rong (2008)
Employing a dynamic Cobb-Douglas total factor productivity function, this study examines the total factor productivity effects of related and unrelated mergers and acquisitions in the United Kingdom for the period 1981-1996. The results indicate that both related and unrelated mergers and acquisitions have a positive impact on the total factor productivity. This study also finds that related mergers tend to perform stronger positive impact on the productivity than unrelated mergers. By controlling size, industry, the length of post merger period or merger waves factors, the evidence show that (1) small firms attain stronger positive productivity impact from M&A than larger firms; (2) the impact on productivity varies across industries, especially unrelated mergers appear better performance in most industries; (3) M&A tend to generate larger long-term effects on total factor productivity than short-run; and (4) firms experienced M&A in 1990s gain stronger productivity impact.